SARS-CoV-2 infection: its psychiatric manifestations - Noel Lorenzo-Villalba; Xavier Jannot; Anezka Syrovatkova; Vincent Michel; Emmanuel Andres (Babol University of Medical Sciences, 2020)
Background:  The clinical presentation of SARS-CoV-2 infection was initially dominated by respiratory symptoms. However the clinical spectrum is wide and neuropsychiatric syndromes are also a source of medical concern. Our aims are to present an atypical clinical presentation of SARS-CoV-2 infection characterized by auditory hallucinations and unusual behavior and to emphasize the diversity of clinical manifestations of SARS-CoV-2 infection. Case Presentation:  A 33-year-old woman was admitted to the emergency department (ED) with a one-day history of auditory hallucinations, unusual behavior, changes in her sleeping habits and incoherent speech. No other symptoms were reported. Blood examinations confirmed high elevated white cell count and C-reactive protein. The head CT scan was normal but the chest scan showed right ground-glass opacities in the lower zones. The oropharyngeal swab was positive for SARS-CoV-2.  Based on these results, the diagnosis of SARS-CoV-2 infection was retained. The patient received no specific treatment for SARS-CoV-2 infection and only needed oxygen therapy support for 7 days. Additional dose of Olanzapine 10 mg daily was initially prescribed but the patient was back to her usual self on day 14 of hospital admission leading to its discontinuation. This clinical course was consistent with a first episode of psychosis triggered by SARS-CoV-2 infection. Conclusions: Neuroinflammation owing to SARS-CoV-2 infection could be responsible for a wide and unknown spectrum of neuropsychiatric manifestations. During this pandemic, special attention should be given to patients with no previous history of psychiatric disorders presenting to ED with neuropsychiatric syndromes of unknown etiology.